The dynamic and distributional aspects of import tariffs - Wolfgang Lechthaler; Mariya Mileva (Kiel Institute for the World Economy (IfW), 2017)
We use a dynamic trade model with two sectors and two types of workers to analyze the optimal setting of income-generating tariffs. This approach allows us to take account of adjustment dynamics, distributional aspects and the time horizon of policy makers and workers. In response to a unilateral increase in tariffs aggregate consumption increases only sluggishly so that policy makers with a short time horizon tend to set lower tariffs. Workers' preferences for tariffs depend on the sector where they are employed as well as their skill class, with the relative weight of both aspects determined by the time horizon of the workers. Unskilled workers in the unskilledintensive sector are the ones most in favor of protectionism and might even benefit from a trade war.
Keywords: F11; F12; F13; 330; protectionism; optimal tariffs; dynamic trade model; inequality